Physiological and genetic control of phytic acid in diverse sets of wheat (Triticum aestivum L.) - Lozano Guajardo, Josefina Concepcion (2021)
Phytic acid (PA) is the main source of phosphorus storage in plants. Since the molecule has a negative charge, it creates complexes with important minerals such as Cu, Zn, Co, Mn, Mg, Fe and Ca. It is therefore regarded as an antinutrient because monogastric animals do not have the necessary enzymes to break the bonds. This leads to major issues such as micronutrient deficiencies in the population, all the unused phosphorus is excreted and eventually reaches water bodies causing eutrophication. Up to 60-85 % of P from soil is stored as PA in grains, hence all this P is removed from the soil at harvest and this removed P has a cost, which has been estimated in billions. Hence, even small reductions in the PA concentrations could represent more efficient and nutritious crops as well as important money savings.